Finding the Art in Systems Conversions, Naming. - Meil, Doug; Aoun, Mario Antoine (Communications of the ACM, 2021)
Excerpts from blog posts written by Ontada software architect Doug Meil about software systems conversions, and by Association for Computing Machinery (ACM) professional member and computer programmer Mario Antoine Aoun about a possible name change for ACM.